Effect of enamel matrix proteins on the treatment of intrabony defects: a split-mouth randomized controlled trial study O efeito da proteína da matriz do esmalte no tratamento de defeitos infra-ósseos: um estudo clínico controlado randomizado boca-dividida - Daniela Chambrone; Ivan Munhoz Pasin; Marina Clemente Conde; Claudio Panutti; Silvia Carneiro; Luiz Antonio Pugliesi Alves de Lima (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The objective of this split-mouth, double-blind, randomized controlled trial was to compare the clinical effect of treatment of 2- or 3-wall intrabony defects with open flap debridement (OFD) combined or not with enamel matrix proteins (EMP). Thirteen volunteers were selected with one pair of or more intrabony defects and probing pocket depth (PPD) > 5 mm. All individuals received instructions regarding oral hygiene and were submitted to scaling and root planing. Each participant received the two treatment modalities: test sites were treated with OFD and EMP, and control sites received only OFD. After 6 months, a significant reduction was observed in PPD for the EMP group (from 6.42 ± 1.08 mm to 2.67 ± 1.15 mm) and for the OFD group (from 6.08 ± 1.00 mm to 2.00 ± 0.95 mm) (p < 0.0001), but with no significant difference between groups (p = 0.13). A significant gain in relative attachment level (RAL) was observed in both groups (EMP: from 13.42 ± 1.88 mm to 10.75 ± 2.26 mm, p < 0.001; OFD: from 12.42 ± 1.98 mm to 10.58 ± 2.23 mm, p = 0.013), but with no significant difference between groups (p = 0.85). Gingival recession (GR) was higher in the EMP group (from 1.08 ± 1.50 mm to 2.33 ± 1.43 mm; p = 0.0009) than in the OFD group (from 0.66 ± 1.15 mm to 1.16 ± 1.33 mm; p = 0.16), but this difference was not significant (p = 0.06). In conclusion, the results showed that OFD combined with EMP was not able to improve treatment of intrabony defects compared to OFD alone. O objetivo deste estudo clínico controlado, randomizado, duplo-cego, tipo boca-dividida foi comparar o efeito clínico do tratamento de defeitos infra-ósseos de 2 ou 3 paredes com retalho de espessura total (RET) associado ou não com a proteína da matriz do esmalte (PME). Treze voluntários com 1 par ou mais de defeitos infra-ósseos foram selecionados com profundidade clínica de sondagem (PCS) > 5 mm. Todos receberam instruções de higiene bucal, raspagem e alisamento radicular. Cada participante recebeu os dois tipos de tratamento: o lado teste foi tratado com RET e PME, e o lado controle recebeu somente RET. Após 6 meses, foi observada uma redução significante na PCS para o grupo PME (de 6,42 ± 1,08 mm para 2,67 ± 1,15 mm) e para o grupo RET (de 6,08 ± 1,00 mm para 2,00 ± 0,95 mm) (p < 0,0001), mas não houve diferença significante entre os grupos (p = 0,13). Um ganho significante de nível clínico de inserção relativo (NCIR) foi observado em ambos os grupos (PME: de 13,42 ± 1,88 mm para 10,75 ± 2,26 mm, p < 0,001; RET: de 12,42 ± 1,98 mm para 10,58 ± 2,23 mm, p = 0,013), mas não houve diferença significante entre os grupos (p = 0,85). A retração gengival (RG) foi maior para o grupo PME (de 1,08 ± 1,50 mm para 2,33 ± 1,43 mm; p = 0,0009) do que para o grupo RET (de 0,66 ± 1,15 mm para 1,16 ± 1,33 mm; p = 0,16), mas essa diferença não foi significante (p = 0,06). Concluiu-se que o tratamento de defeitos infra-ósseos com RET associado à PME não mostrou resultados melhores que o uso de RET sozinho.